2006
DOI: 10.1093/ajcn/83.2.355
|View full text |Cite
|
Sign up to set email alerts
|

Green tea consumption and cognitive function: a cross-sectional study from the Tsurugaya Project

Abstract: A higher consumption of green tea is associated with a lower prevalence of cognitive impairment in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
245
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 378 publications
(255 citation statements)
references
References 32 publications
8
245
0
2
Order By: Relevance
“…Conversely, a Japanese study (13) found no association between coffee consumption and depressive symptoms. The lack of an association in the Japanese study may be partly ascribed to infrequent consumption of coffee among the elderly, with only 13?2 % of the study participants consuming $2 cups coffee/d, as reported in an earlier study that included the same participants (30) . A null finding has also been reported from a Finnish study (18) .…”
Section: Discussionmentioning
confidence: 67%
“…Conversely, a Japanese study (13) found no association between coffee consumption and depressive symptoms. The lack of an association in the Japanese study may be partly ascribed to infrequent consumption of coffee among the elderly, with only 13?2 % of the study participants consuming $2 cups coffee/d, as reported in an earlier study that included the same participants (30) . A null finding has also been reported from a Finnish study (18) .…”
Section: Discussionmentioning
confidence: 67%
“…The first study analyzed data from 1003 Japanese subjects (470 years), who gave information about the frequency of green tea consumption, whereas their cognitive function was evaluated by using the Mini-Mental State Examination test. 4 The authors found that higher consumption of green tea is associated with a lower prevalence of cognitive impairment. Comparable results were obtained in another study including 2501 Chinese aged 455 years.…”
Section: Introductionmentioning
confidence: 99%
“…Following a request from the European Commission, the Panel on Dietetic Products, Nutrition and Allergies was asked to provide a scientific opinion on a list of health claims pursuant to Article 13 of Regulation (EC) No 1924No /2006. This opinion addresses the scientific substantiation of health claims in relation to L-theanine from Camellia sinensis (L.) Kuntze (tea) and improvement of cognitive function, alleviation of psychological stress, maintenance of normal sleep and reduction of menstrual discomfort.…”
Section: Discussionmentioning
confidence: 99%